Positive electrode for nonaqueous electrolyte power storage element, method for manufacturing the same, and nonaqueous electrolyte power storage element
The use of a water-soluble binder with high content in the positive electrode of nonaqueous electrolyte storage devices addresses the challenge of maintaining conductive paths during volume changes in sulfur-based active materials, resulting in enhanced initial and cyclic discharge capacities and high-rate discharge performance.
Patent Information
- Application Number
- JP2023178162
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-16
- Publication Date
- 2025-04-28
AI Technical Summary
Existing nonaqueous electrolyte storage devices with sulfur-based positive electrodes face challenges in achieving high initial discharge capacity and maintaining performance after charge/discharge cycles due to volume changes in sulfur-based active materials, which disrupt the conductive path.
A positive electrode for nonaqueous electrolyte storage devices is developed, featuring a sulfur-based active material layer with a water-soluble binder content of 50% or more by mass, and a binder content of 1% to 10% by mass in the active material layer, which enhances the binder's ability to adapt to volume changes and maintain the conductive path.
The proposed solution increases the initial discharge capacity and maintains high discharge capacity after charge/discharge cycles, while also improving high-rate discharge performance of the nonaqueous electrolyte storage devices.
Smart Images

Figure 2025068336000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode for a nonaqueous electrolyte storage element, a method for producing the same, and a nonaqueous electrolyte storage element. [Background technology]
[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. Non-aqueous electrolyte secondary batteries generally have a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring charge-transporting ions such as lithium ions between the two electrodes. As non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used.
[0003] Known non-aqueous electrolyte storage elements include lithium-sulfur batteries (Li-S batteries) and other non-aqueous electrolyte storage elements that use a sulfur-based active material in the positive electrode. Patent Document 1 describes a positive electrode for a lithium-sulfur battery that includes a positive electrode active material that includes sulfur, a sulfur-based compound, or a mixture thereof, a conductive agent, and a binder that includes a styrene-based rubber. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-223897 A Summary of the Invention [Problem to be solved by the invention]
[0005] Sulfur-based active materials have a large theoretical capacity, and nonaqueous electrolyte electricity storage elements using sulfur-based active materials in the positive electrodes are expected to have high energy density. However, even in nonaqueous electrolyte electricity storage elements having positive electrodes using sulfur-based active materials, further improvements in discharge capacity and the like are expected.
[0006] An object of the present invention is to provide a positive electrode for a nonaqueous electrolyte storage element, which is a positive electrode using a sulfur-based active material and can increase the initial discharge capacity of the nonaqueous electrolyte storage element, as well as a method for producing such a positive electrode and a nonaqueous electrolyte storage element including such a positive electrode. [Means for solving the problem]
[0007] A positive electrode for a non-aqueous electrolyte storage element according to one aspect of the present invention includes a positive electrode active material layer including a sulfur-based active material and a binder, the binder including a water-soluble binder, the content of the water-soluble binder relative to the binder being 50% by mass or more, and the content of the binder relative to the positive electrode active material layer being 1% by mass or more and less than 10% by mass.
[0008] A method for manufacturing a positive electrode for a non-aqueous electrolyte storage element according to another aspect of the present invention includes applying a positive electrode mixture paste containing a sulfur-based active material, a binder, and water, wherein the binder includes a water-soluble binder, the content of the water-soluble binder relative to the binder is 50 mass% or more, and the content of the binder relative to the solid content in the positive electrode mixture paste is 1 mass% or more and less than 10 mass%.
[0009] A nonaqueous electrolyte storage element according to another aspect of the present invention includes the positive electrode for the nonaqueous electrolyte storage element according to the aspect of the present invention. Effect of the Invention
[0010] According to one aspect of the present invention, it is possible to provide a positive electrode for a nonaqueous electrolyte storage element, which is a positive electrode using a sulfur-based active material and can increase the initial discharge capacity of the nonaqueous electrolyte storage element, as well as a method for producing such a positive electrode and a nonaqueous electrolyte storage element including such a positive electrode. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a perspective view showing one embodiment of a nonaqueous electrolyte electricity storage element. [Diagram 2] FIG. 2 is a schematic diagram showing one embodiment of an electricity storage device formed by assembling a plurality of nonaqueous electrolyte electricity storage elements. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] First, an outline of the positive electrode for a nonaqueous electrolyte storage element, the method for producing the positive electrode for a nonaqueous electrolyte storage element, and the nonaqueous electrolyte storage element disclosed in this specification will be described.
[0013] [1] A positive electrode for a non-aqueous electrolyte storage element according to one aspect of the present invention includes a positive electrode active material layer including a sulfur-based active material and a binder, the binder including a water-soluble binder, the content of the water-soluble binder relative to the binder being 50% by mass or more, and the content of the binder relative to the positive electrode active material layer being 1% by mass or more and less than 10% by mass.
[0014] The positive electrode for a non-aqueous electrolyte storage element described in [1] above is a positive electrode using a sulfur-based active material, and can increase the initial discharge capacity of the non-aqueous electrolyte storage element. The reason for this is unclear, but the following reason is speculated. The sulfur-based active material is an active material that undergoes a large volume change with charging and discharging. For this reason, in a conventional positive electrode using a sulfur-based active material, the binder cannot sufficiently follow the volume change of the sulfur-based active material with charging and discharging, and the conductive path in the positive electrode is easily broken during chemical conversion treatment after the non-aqueous electrolyte storage element is assembled. The chemical conversion treatment refers to the first discharge of a non-aqueous electrolyte storage element that has not been charged or discharged after assembly. Such a break in the conductive path is considered to be one of the factors that leads to a decrease in the initial discharge capacity. On the other hand, the water-soluble binder is a binder that has high coverage or adhesion to the sulfur-based active material. Therefore, in a positive electrode using a sulfur-based active material, by using 50% by mass or more of a water-soluble binder as a binder, the binder's ability to follow the volume change of the sulfur-based active material is improved, and the disconnection of the conductive path during the chemical conversion treatment, which is the first discharge, is suppressed. Furthermore, in the positive electrode for a nonaqueous electrolyte storage element described in [1] above, the binder content relative to the positive electrode active material layer is 1% by mass or more and less than 10% by mass, so that excessive coating of the sulfur-based active material is suppressed and a sufficient reaction area is ensured. For these reasons, it is presumed that the positive electrode for a nonaqueous electrolyte storage element described in [1] above can increase the initial discharge capacity of the nonaqueous electrolyte storage element.
[0015] In addition, the positive electrode for a non-aqueous electrolyte storage element described in [1] above can also increase the discharge capacity after charge / discharge cycles. Although the reason for this is unclear, it is presumed that this is due to the fact that the water-soluble binder has high coverage for the sulfur-based active material, as described above, and that the breakage of the conductive path caused by repeated charge / discharge is suppressed. Furthermore, the positive electrode for a non-aqueous electrolyte storage element described in [1] above can improve the high-rate discharge performance of the non-aqueous electrolyte storage element. Although the reason for this is unclear, it is presumed that this is due to the fact that the water-soluble binder has high coverage for the sulfur-based active material, as described above.
[0016] The type and content of the binder in the positive electrode active material layer can be specified by the following procedure. The nonaqueous electrolyte storage element is disassembled, and the positive electrode is taken out. The nonaqueous electrolyte attached to the taken out positive electrode is thoroughly washed using dimethyl carbonate, and the positive electrode is dried under reduced pressure at room temperature for 24 hours. After drying, the positive electrode active material layer is collected. The collected positive electrode active material layer is used as an analysis sample, and is analyzed by a pyrolysis gas chromatography-mass spectrometer (PyGC-MS) to identify the type of binder. The analysis sample is also analyzed by a thermogravimetry (TG) to determine the binder content. Specifically, the analysis sample is heated from room temperature at a constant rate of 5°C / min or less while replacing the atmosphere in the sample chamber with helium gas at a constant rate of 300mL / min or less, and the temperature at which the weight changes and the amount of weight change are measured to quantitatively determine the content of each binder.
[0017] [2] In the positive electrode for a nonaqueous electrolyte storage element according to the above [1], the binder may further contain a water-dispersible rubber.
[0018] The positive electrode for a nonaqueous electrolyte storage element described in [2] above can increase the initial discharge capacity of the nonaqueous electrolyte storage element. Although the reason for this is unclear, it is presumed that the use of a water-soluble binder of 50 mass % or more in combination with a water-dispersible rubber as the binder optimizes the amount and state of coating of the binder on the sulfur-based active material.
[0019] [3] In the positive electrode for a nonaqueous electrolyte storage element according to the above [2], a total content of the water-soluble binder and the water-dispersible rubber relative to the binder may be 90 mass % or more.
[0020] The positive electrode for a nonaqueous electrolyte storage element according to the above item [3] can further enhance the above-mentioned effects relating to the initial discharge capacity and after charge / discharge cycles, and the high-rate discharge performance.
[0021] [4] In the positive electrode for a nonaqueous electrolyte storage element according to any one of the above [1] to [3], the water-soluble binder may be at least one selected from the group consisting of poly(meth)acrylic acid and salts thereof.
[0022] The positive electrode for a nonaqueous electrolyte storage element according to the above item [4] can further enhance the above-mentioned effects relating to the initial discharge capacity and after charge / discharge cycles, and the high-rate discharge performance.
[0023] [5] In the positive electrode for a nonaqueous electrolyte storage element according to the above item [2] or [3], the water-dispersible rubber may be a diene rubber.
[0024] The positive electrode for a nonaqueous electrolyte storage element according to the above item [5] can further enhance the above-mentioned effects relating to the initial discharge capacity and after charge-discharge cycles, and the high-rate discharge performance.
[0025] [6] In the positive electrode for a nonaqueous electrolyte storage element according to any one of [1] to [5] above, the positive electrode active material layer may further contain porous carbon forming a complex with the sulfur-based active material.
[0026] The positive electrode for a nonaqueous electrolyte storage element described in [6] above has high electronic conductivity due to the sulfur-based active material forming a composite with the porous carbon, and can further enhance the above-mentioned effects related to the initial discharge capacity and after charge-discharge cycles as well as the high-rate discharge performance.
[0027] [7] A method for manufacturing a positive electrode for a non-aqueous electrolyte storage element according to another aspect of the present invention includes applying a positive electrode mixture paste containing a sulfur-based active material, a binder, and water, wherein the binder includes a water-soluble binder, the content of the water-soluble binder relative to the binder is 50 mass% or more, and the content of the binder relative to a solid content in the positive electrode mixture paste is 1 mass% or more and less than 10 mass%.
[0028] According to the method for producing a positive electrode for a nonaqueous electrolyte storage element described in [7] above, a positive electrode that can increase the initial discharge capacity of a nonaqueous electrolyte storage element can be produced. In addition, the positive electrode obtained by the method for producing a positive electrode for a nonaqueous electrolyte storage element described in [7] above can increase the discharge capacity of the nonaqueous electrolyte storage element after charge-discharge cycles and improve the high-rate discharge performance.
[0029] The "solid content" in the positive electrode mixture paste refers to components other than water and any other dispersion medium.
[0030] [8] A nonaqueous electrolyte storage element according to another aspect of the present invention includes the positive electrode for the nonaqueous electrolyte storage element according to any one of [1] to [6] above.
[0031] The nonaqueous electrolyte storage element described in [8] above has a large initial discharge capacity. In addition, the nonaqueous electrolyte storage element described in [8] above also has a large discharge capacity after charge-discharge cycles and has high high-rate discharge performance.
[0032] [9] The nonaqueous electrolyte storage element according to the above [8] may further include a negative electrode containing metallic lithium.
[0033] The nonaqueous electrolyte electricity storage element described in [9] above has a negative electrode containing metallic lithium, and thus has further advantages such as high energy density.
[0034]
[10] The nonaqueous electrolyte storage element according to the above [8] or [9] may further include a nonaqueous electrolyte containing a nonaqueous solvent mainly composed of a carbonate.
[0035] The nonaqueous electrolyte storage element according to the above item
[10] can further enhance the above-mentioned effects relating to the initial discharge capacity and after charge / discharge cycles, and the high-rate discharge performance.
[0036] The "major component" in the non-aqueous solvent means a component whose content in the non-aqueous solvent is 50% by volume or more.
[0037] The type and content of the non-aqueous solvent contained in the non-aqueous electrolyte are identified by liquid chromatography-mass spectrometry (LC-MS) and gas chromatography-mass spectrometry (GC-MS). Specifically, this is done as follows. The LC-MS and GC-MS measurements are performed consecutively under the same conditions. (1) Collection of non-aqueous electrolyte First, the nonaqueous electrolyte storage element is disassembled to remove the nonaqueous electrolyte. If the nonaqueous electrolyte cannot be removed, the nonaqueous electrolyte storage element is centrifuged to remove the nonaqueous electrolyte. If the nonaqueous electrolyte cannot be removed even after centrifugation, an appropriate extraction solvent (e.g., acetonitrile) is injected into the nonaqueous electrolyte storage element, and the nonaqueous electrolyte diluted with the extraction solvent is removed. (2)LC-MS The components of the collected non-aqueous electrolyte are analyzed by LC-MS. The LC-MS analysis is performed in the following order of qualitative analysis and quantitative analysis. The LC-MS analysis is performed using Waters' "Acquity H" and "Xevo G2-5QTof" instruments. Water is used as the eluent. (qualitative analysis) The measurement sample (non-aqueous electrolyte) is subjected to LC-MS analysis. If the peaks in the obtained liquid chromatogram cannot be separated, a GC-MS analysis, described below, is performed instead of the LC-MS analysis. If the peaks can be separated, the components contained in the measurement sample are predicted from the MS spectrum of each peak. A known sample of the predicted components (hereinafter referred to as "predicted components") is subjected to LC-MS analysis. The retention times and MS spectrum of the peaks corresponding to each predicted component in the measurement sample are compared with the retention times and MS spectrum of the peaks of a known sample of the predicted components, and if they match, the prediction is presumed to be correct. (Quantitative analysis) Quantitative analysis is performed using the calibration curve method. First, a known sample of the predicted component with a known concentration is measured by LC-MS, and a calibration curve is created by calculating the peak area. The calibration curve is calculated using the coefficient of determination (r 2) is created so that it is between 0.999 and 1. The amount of the predicted component in the measurement sample is calculated from the calibration curve and the area of the peak of the predicted component in the measurement sample. The above process is performed for all peaks detected in the LC-MS analysis of the measurement sample, and the amount of each predicted component is calculated. (3)GC-MS The GC-MS analysis is carried out in the following order: qualitative analysis and quantitative analysis. The GC-MS analysis equipment used is the Agilent 5975C. Argon is used as the carrier gas. (qualitative analysis) A measurement sample (non-aqueous electrolyte) is subjected to GC-MS analysis. The components contained in the sample are predicted from the MS spectrum of each peak in the obtained gas chromatogram. A known sample of the predicted components is subjected to GC-MS analysis. The retention time and MS spectrum of the peak corresponding to the predicted component in the measurement sample are compared with the retention time and MS spectrum of the peak of a known sample of the predicted component, and if they match, the above prediction is presumed to be correct. (Quantitative analysis) The quantitative analysis is performed by the calibration curve method. The quantitative analysis by GC-MS is performed in the same manner as the quantitative analysis by LC-MS described above, and the content of each predicted component is determined. (4) Calculation of the content of each component The total amount of nonaqueous solvent is calculated by summing the contents of each nonaqueous solvent in each predicted component (i.e., each component) measured by LC-MS or GC-MS. Note that, when calculating the content (volume %) of each nonaqueous solvent relative to the total amount of nonaqueous solvent, the mass-based content of each nonaqueous solvent measured by LC-MS or GC-MS is converted to a volume at 20°C, and the total amount of nonaqueous solvent is calculated by summing the volume-converted contents of each nonaqueous solvent. In addition, when an extraction solvent is used, the extraction solvent is excluded from the calculation.
[0038] A positive electrode for a nonaqueous electrolyte storage element according to one embodiment of the present invention, a method for manufacturing a positive electrode for a nonaqueous electrolyte storage element, a nonaqueous electrolyte storage element, an electricity storage device, a method for manufacturing a nonaqueous electrolyte storage element, and other embodiments will be described in detail. Note that the names of the components (components) used in each embodiment may differ from the names of the components (components) used in the background art.
[0039] <Positive electrode for non-aqueous electrolyte storage element> A positive electrode for a nonaqueous electrolyte storage element according to one embodiment of the present invention (hereinafter, also simply referred to as "positive electrode") has a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer. The positive electrode is used in a nonaqueous electrolyte storage element, and is preferably used in a nonaqueous electrolyte secondary battery. The nonaqueous electrolyte secondary battery may be a lithium ion secondary battery or a lithium-sulfur battery. The nonaqueous electrolyte storage element is preferably a nonaqueous electrolyte storage element, and more preferably a nonaqueous electrolyte secondary battery.
[0040] The positive electrode substrate is conductive. Whether or not it has "conductivity" is determined by whether the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 -2 The threshold value is Ω·cm. The material of the positive electrode substrate is a metal such as aluminum, titanium, tantalum, stainless steel, or an alloy thereof. Among these, aluminum or an aluminum alloy is preferred from the viewpoints of potential resistance, high conductivity, and cost. The positive electrode substrate may be a foil, a vapor deposition film, a mesh, a porous material, etc., and a foil is preferred from the viewpoint of cost. Therefore, aluminum foil or an aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or an aluminum alloy include A1085, A3003, A1N30, etc., as specified in JIS-H-4000 (2014) or JIS-H-4160 (2006).
[0041] The average thickness of the positive electrode substrate is preferably 3 μm or more and 50 μm or less, more preferably 5 μm or more and 40 μm or less, even more preferably 8 μm or more and 30 μm or less, and particularly preferably 10 μm or more and 25 μm or less. By setting the average thickness of the positive electrode substrate within the above range, it is possible to increase the strength of the positive electrode substrate while increasing the energy density per mass or volume of the positive electrode. The "average thickness" refers to the average value of thicknesses measured at any five points.
[0042] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer contains a conductive agent such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and may contain, for example, a binder and a conductive agent.
[0043] The positive electrode active material layer includes a sulfur-based active material and a binder. The positive electrode active material layer includes optional components such as a conductive agent, a dispersant, and a filler, as necessary. The positive electrode active material layer is usually formed from a positive electrode mixture including a sulfur-based active material, a binder, and other optional components.
[0044] The sulfur-based active material is a component that functions as a positive electrode active material. The sulfur-based active material may be sulfur alone, a sulfur compound, or a mixture thereof. Examples of the sulfur compound include metal sulfides such as lithium sulfide, organic disulfide compounds, and organic sulfur compounds such as carbon sulfide compounds. The sulfur-based active material has the advantages of a large theoretical capacity and low cost.
[0045] The content of the sulfur-based active material in the positive electrode active material layer is preferably 50% by mass to 90% by mass, more preferably 60% by mass to 80% by mass. By having the content of the sulfur-based active material in the above range, it is possible to increase the initial discharge capacity and the discharge capacity after the charge-discharge cycle, and to improve the high-rate discharge performance.
[0046] The positive electrode active material layer preferably further contains porous carbon forming a complex with the sulfur-based active material. In other words, the sulfur-based active material is preferably contained in the positive electrode active material layer as a complex with the porous carbon. Hereinafter, the complex of the sulfur-based active material and the porous carbon is also simply referred to as a "complex". In the complex, the sulfur-based active material is usually supported in the pores of the porous carbon. By the complex being in such a form, sufficient electronic conductivity is ensured. The complex may be substantially composed of only the sulfur-based active material and the porous carbon, or may be substantially composed of only the sulfur-based active material and the porous carbon. The complex substantially composed of only the sulfur-based active material and the porous carbon means, for example, that the total content of the sulfur-based active material (total of simple sulfur and sulfur compound) and the porous carbon in the complex is 90% by mass or more, and may be 95% by mass or more, 98% by mass or more, or 99% by mass or more.
[0047] The content of the sulfur-based active material in the composite is preferably 50% by mass to 90% by mass, more preferably 60% by mass to 80% by mass. By setting the content of the sulfur-based active material in the composite within the above range, it is possible to increase the initial discharge capacity and the discharge capacity after the charge-discharge cycle, and to improve the high-rate discharge performance.
[0048] Porous carbon has electrical conductivity. Porous carbon is generally a porous inorganic material whose main constituent element is carbon. The main constituent element refers to the element that is most abundant on a mass basis. The lower limit of the carbon element content in the porous carbon is preferably 70 mass%, more preferably 80 mass%, 90 mass%, 95 mass% or 97 mass%. The upper limit of the carbon element content in the porous carbon may be 100 mass% or 99.9 mass%. The carbon element content in the porous carbon may be a combination of any of the above lower limits and the above upper limit. The porous carbon may contain elements other than carbon, such as oxygen and nitrogen.
[0049] The composite can be produced by a conventional method, for example, by heating a mixture of a sulfur-based active material and porous carbon to a temperature equal to or higher than the melting point of the sulfur-based active material, and then cooling the mixture.
[0050] The content of the composite in the positive electrode active material layer is preferably 60% by mass to 97% by mass, more preferably 80% by mass to 96% by mass, and even more preferably 90% by mass to 95% by mass. By setting the content of the composite in the above range, it is possible to increase the initial discharge capacity and the discharge capacity after the charge / discharge cycle, and to improve the high-rate discharge performance.
[0051] The positive electrode active material layer may contain a positive electrode active material other than the sulfur-based active material, but the content of the sulfur-based active material in the total positive electrode active material is preferably 50 mass% or more, more preferably 70 mass% or more, even more preferably 90 mass% or more, even more preferably 99 mass% or more, and particularly preferably 100 mass%.
[0052] The binder includes a water-soluble binder. The water-soluble binder is a binder that dissolves at least 1 part by mass in 100 parts by mass of water at 20°C. Examples of the water-soluble binder include poly(meth)acrylic acid, a salt of poly(meth)acrylic acid, polyvinyl alcohol, polyethylene oxide, and polypropylene oxide. The water-soluble binder is preferably at least one selected from the group consisting of poly(meth)acrylic acid and its salts, and more preferably at least one selected from the group consisting of polyacrylic acid and its salts. Examples of the salt of poly(meth)acrylic acid include metal salts such as sodium salts, and ammonium salts. One or more types of water-soluble binders can be used.
[0053] The lower limit of the content of the water-soluble binder relative to the binder is 50 mass%, preferably 60 mass%, and more preferably 70 mass%. By setting the content of the water-soluble binder to the above lower limit or more, the initial discharge capacity and the discharge capacity after the charge-discharge cycle can be increased, and the high-rate discharge performance can be improved. From the viewpoint of increasing the discharge capacity after the charge-discharge cycle and the high-rate discharge performance, the lower limit of the content of the water-soluble binder is more preferably 80 mass%, 90 mass%, or 95 mass%. The upper limit of the content of the water-soluble binder relative to the binder may be 100 mass%. From the viewpoint of increasing the initial discharge capacity, the upper limit of the content of the water-soluble binder is preferably 95 mass%, 90 mass%, 85 mass%, 80 mass%, or 75 mass%. The content of the water-soluble binder relative to the binder can be a combination of any of the above lower limits and any of the above upper limits (however, the lower limit is smaller than the upper limit).
[0054] The binder preferably further contains a water-dispersible rubber. The initial discharge capacity can be increased by including the water-dispersible rubber in the binder. The water-dispersible rubber is a rubber that disperses at 1 part by mass or more in 100 parts by mass of water at 20°C. The water-dispersible rubber also includes, for example, a rubber that disperses at 1 part by mass or more in 100 parts by mass of water at 20°C when used in combination with a dispersant. Examples of the water-dispersible rubber include diene-based rubbers such as styrene-butadiene rubber, ethylene-propylene-diene rubber, and nitrile-butadiene rubber, fluororubber, and acrylic rubber. The diene-based rubber is usually a rubber that contains a diene such as butadiene or isoprene as one of the monomers. The diene-based rubber may be a rubber having a carbon-carbon double bond in the main chain. As the water-dispersible rubber, a diene-based rubber is preferable, and a styrene-butadiene rubber is more preferable. One or more types of water-dispersible binders can be used.
[0055] When using a water-dispersible rubber, the lower limit of the content of the water-dispersible rubber relative to the binder is preferably 5% by mass, and may be more preferably 10% by mass or 20% by mass. By making the content of the water-dispersible rubber equal to or greater than the above lower limit, the initial discharge capacity can be increased. The upper limit of the content of the water-dispersible rubber relative to the binder is 50% by mass, and may be 40% by mass, 30% by mass, 20% by mass, 10% by mass, 5% by mass, or 2% by mass. By making the content of the water-dispersible rubber equal to or less than the above upper limit, the discharge capacity after the charge-discharge cycle can be increased and the high-rate discharge performance can be improved. The content of the water-dispersible rubber relative to the binder can be a combination of any of the above lower limits and any of the above upper limits (however, the lower limit is smaller than the upper limit).
[0056] The binder may further include binders other than the water-soluble binder and the water-dispersible rubber. However, the lower limit of the total content of the water-soluble binder and the water-dispersible rubber relative to the binder is preferably 90% by mass, more preferably 95% by mass, and even more preferably 99% by mass. In this way, by substantially not using binders other than the water-soluble binder and the water-dispersible rubber as the binder, it is possible to increase the initial discharge capacity and the discharge capacity after the charge-discharge cycle, and to improve the high-rate discharge performance.
[0057] The lower limit of the binder content in the positive electrode active material layer is 1 mass%, preferably 3 mass%, more preferably 4 mass%, and further preferably 5 mass%. By setting the binder content to the above lower limit or more, the sulfur-based active material and the like can be sufficiently held. The binder content in the positive electrode active material layer is less than 10 mass%. The upper limit of the binder content in the positive electrode active material layer may be 9 mass%, or may be 8 mass%, 7 mass%, 6 mass%, or 5 mass%. By setting the binder content to the above upper limit or less, the sulfur-based active material is prevented from being excessively covered with the binder, and the initial discharge capacity can be increased. The binder content in the positive electrode active material layer can be a combination of any of the above lower limits and any of the above upper limits (however, the lower limit is smaller than the upper limit). The binder does not include the polysaccharide polymer described later. The binder may be any polymer other than the polysaccharide polymer. The binder may be any polymer other than the polysaccharide polymer and the filler. The binder may be poly(meth)acrylic acid, its salts and diene-based rubbers.
[0058] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. The conductive agent does not include porous carbon constituting the composite. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, and the like. Examples of carbonaceous materials include graphite, non-graphitic carbon, graphene-based carbon, and the like. Examples of non-graphitic carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotubes (carbon nanotubes: CNT), fullerene, and the like. Examples of the conductive agent include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. These materials may also be used in a composite form. For example, a material in which carbon black and CNT are composited may be used. Among these, carbon black is preferable from the viewpoint of electronic conductivity and coatability, and acetylene black is preferable among them. It is also preferable to use carbon black (preferably acetylene black) in combination with CNT.
[0059] The content of the conductive agent (excluding the porous carbon in the composite) in the positive electrode active material layer is preferably 0.5% by mass or more and 15% by mass or less, more preferably 1% by mass or more and 10% by mass or less. The upper limit of the content of the conductive agent in the positive electrode active material layer may be 5% by mass or 3% by mass. By setting the content of the conductive agent in the above range, the energy density per mass of the positive electrode can be increased.
[0060] Examples of the dispersant include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the dispersant has a functional group that reacts with lithium or the like, the functional group may be deactivated in advance by methylation or the like. The content of the dispersant in the positive electrode active material layer is preferably 0.05% by mass or more and 5% by mass or less, more preferably 0.1% by mass or more and 2% by mass or less. The polysaccharide polymer may function as a thickener.
[0061] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, alumina, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and artificial products thereof. When the positive electrode active material layer contains a filler, the content of the filler in the positive electrode active material layer is preferably, for example, 0.1% by mass or more and 10% by mass or less. In one embodiment of the present invention, the positive electrode active material layer may not contain a filler.
[0062] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W, as components other than the sulfur-based active material, other positive electrode active materials, porous carbon, binder, conductive agent, dispersant, and filler.
[0063] The mass per unit area of the positive electrode active material layer is not particularly limited, but is preferably 1 mg / cm 2 More than 30mg / cm 2 Less than 5 mg / cm is preferred. 2 More than 25mg / cm 2 Less than 10 mg / cm is more preferable. 2 More than 20mg / cm 2The following is more preferable. By setting the mass per unit area of the positive electrode active material layer within the above range, it is possible to optimize the initial discharge capacity and the discharge capacity after the charge / discharge cycle, the high-rate discharge performance, the energy density, etc. in a well-balanced manner. The "mass per unit area of the positive electrode active material layer" refers to the mass per unit area of one positive electrode active material layer. For example, when the positive electrode active material layers are provided on both sides of the positive electrode substrate, the "mass per unit area of the positive electrode active material layer" refers to the value per one side.
[0064] <Method of manufacturing positive electrode for non-aqueous electrolyte storage element> A method for manufacturing a positive electrode for a non-aqueous electrolyte storage element according to one embodiment of the present invention includes applying a positive electrode mixture paste containing a sulfur-based active material, a binder, and water, wherein the binder includes a water-soluble binder, the content of the water-soluble binder relative to the binder is 50 mass% or more, and the content of the binder relative to a solid content in the positive electrode mixture paste is 1 mass% or more and less than 10 mass%.
[0065] The positive electrode mixture paste may further contain each component constituting the positive electrode active material layer in addition to the sulfur-based active material and the binder. The specific form and preferred form of each component contained in the positive electrode mixture paste are the same as each component contained in the positive electrode active material layer. Water in the positive electrode mixture paste is a dispersion medium. The positive electrode mixture paste may further contain a dispersion medium other than water.
[0066] The positive electrode mixture paste is applied to the positive electrode substrate directly or via an intermediate layer. After application, drying, pressing, etc. may be performed. The applied positive electrode mixture paste is dried to form a positive electrode active material layer.
[0067] <Non-aqueous electrolyte electricity storage element> A nonaqueous electrolyte storage element (hereinafter, also simply referred to as "storage element") according to one embodiment of the present invention includes an electrode assembly having a positive electrode, a negative electrode, and a separator, a nonaqueous electrolyte, and a container that contains the electrode assembly and the nonaqueous electrolyte. The electrode assembly is usually a laminated type in which a plurality of positive electrodes and a plurality of negative electrodes are laminated with a separator interposed therebetween, or a wound type in which a positive electrode and a negative electrode are laminated with a separator interposed therebetween and wound. At least a part of the nonaqueous electrolyte exists in a state in which it is permeated into the voids of the positive electrode, the negative electrode, and the separator. As an example of a nonaqueous electrolyte storage element, a nonaqueous electrolyte secondary battery (hereinafter, also simply referred to as "secondary battery") will be described.
[0068] (positive electrode) The positive electrode provided in the nonaqueous electrolyte storage element according to one embodiment of the present invention is the same as that described above as the positive electrode for the nonaqueous electrolyte storage element according to one embodiment of the present invention.
[0069] (Negative electrode) The negative electrode has a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The configuration of the intermediate layer is not particularly limited and can be selected from the configurations exemplified for the positive electrode.
[0070] The negative electrode substrate has electrical conductivity. Metals such as copper, nickel, stainless steel, and nickel-plated steel, or alloys thereof, and carbonaceous materials are used as the material of the negative electrode substrate. Among these, nickel or nickel alloys are preferred. Examples of the negative electrode substrate include foil, vapor deposition film, mesh, and porous materials, and foil is preferred from the viewpoint of cost. Therefore, nickel foil or nickel alloy foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil.
[0071] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, it is possible to increase the strength of the negative electrode substrate and to increase the energy density per volume of the nonaqueous electrolyte storage element.
[0072] The negative electrode active material layer includes a negative electrode active material. The negative electrode active material layer includes optional components such as a conductive agent, a binder, a dispersant, and a filler as necessary. The optional components such as the conductive agent, the dispersant, and the filler can be selected from the materials exemplified for the positive electrode. The binder in the negative electrode active material layer is not limited to a water-soluble binder, and a known binder can be used. The binder in the negative electrode active material layer may be a water-soluble binder or a water-dispersible rubber exemplified for the positive electrode, or another binder. The negative electrode active material layer may not include optional components such as a conductive agent, a binder, a dispersant, and a filler.
[0073] The negative electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, dispersant, and filler.
[0074] The negative electrode active material can be appropriately selected from known negative electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the negative electrode active material for lithium ion secondary batteries. Examples of the negative electrode active material include metallic lithium; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; Li 4 Ti 5 O 12 , LiTiO 2、 TiNb 2 O 7 Examples of the negative electrode active material include titanium-containing oxides such as titanium oxide, polyphosphate compounds, silicon carbide, and carbon materials such as graphite and non-graphitic carbon (easily graphitizable carbon or non-graphitizable carbon). In the case of a negative electrode active material that does not contain lithium ions, a material doped with charge transport ions such as lithium ions can be used.
[0075] Metallic lithium is preferred as the negative electrode active material. Metallic lithium may be pure metallic lithium consisting essentially of lithium element, or may be a lithium alloy containing other metal elements. Examples of the lithium alloy include a lithium silver alloy, a lithium zinc alloy, a lithium calcium alloy, a lithium aluminum alloy, a lithium magnesium alloy, and a lithium indium alloy. The lithium alloy may contain a plurality of metal elements other than the lithium element.
[0076] The negative electrode active material layer may contain other negative electrode active materials than metallic lithium. However, the negative electrode active material layer is preferably a layer substantially composed of metallic lithium (pure metallic lithium or lithium alloy). The lower limit of the content of lithium element in the negative electrode active material layer is preferably 80 mass%, more preferably 90 mass%, and even more preferably 99 mass%. The upper limit of the content of lithium element in the negative electrode active material layer may be 100 mass%. The content of lithium element in the negative electrode active material layer may be a combination of any of the above lower limits and the above upper limit.
[0077] The negative electrode active material layer may be a non-porous layer (solid layer) or a porous layer, but is preferably a non-porous layer. The negative electrode active material layer may be a layer of metallic lithium. The negative electrode active material layer may be a layer made of metallic lithium foil (pure metallic lithium foil or lithium alloy foil). The average thickness of the negative electrode active material layer in a charged state is preferably 5 μm or more and 2,000 μm or less, more preferably 30 μm or more and 1,200 μm or less, and even more preferably 100 μm or more and 800 μm or less. The "average thickness of the negative electrode active material layer in a charged state" refers to the average thickness of one layer of the negative electrode active material layer in a charged state. For example, when the negative electrode active material layer is provided on both sides of the negative electrode substrate, the "average thickness of the negative electrode active material layer in a charged state" refers to the value per one side.
[0078] (Separator) The separator can be appropriately selected from known separators. For example, a separator consisting of only a substrate layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both surfaces of the substrate layer, etc. can be used as the separator. Examples of the shape of the substrate layer of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these shapes, a porous resin film is preferred from the viewpoint of strength, and a nonwoven fabric is preferred from the viewpoint of non-aqueous electrolyte retention. As the material of the substrate layer of the separator, polyolefins such as polyethylene and polypropylene are preferred from the viewpoint of shutdown function, and polyimide and aramid are preferred from the viewpoint of oxidation decomposition resistance. A material obtained by combining these resins may be used as the substrate layer of the separator.
[0079] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500° C. in an air atmosphere at 1 atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800° C. Examples of materials that have a mass loss of a predetermined amount or less include inorganic compounds. That is, the heat-resistant layer may be an inorganic particle layer containing inorganic particles and a binder. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicates; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; poorly soluble ionic crystals such as calcium fluoride, barium fluoride, and barium titanate; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof. As inorganic compounds, these substances may be used alone or in combination of two or more. Among these inorganic compounds, silicon oxide, aluminum oxide, and aluminosilicate are preferred from the viewpoint of safety of the nonaqueous electrolyte storage element.
[0080] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.
[0081] As the separator, a polymer gel composed of a polymer and a non-aqueous electrolyte may be used. Examples of the polymer include polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, and polyvinylidene fluoride. The use of the polymer gel has an effect of suppressing leakage. As the separator, the above-mentioned porous resin film or nonwoven fabric may be used in combination with the polymer gel.
[0082] (Non-aqueous electrolyte) The nonaqueous electrolyte can be appropriately selected from known nonaqueous electrolytes. In general, a nonaqueous electrolyte solution containing a nonaqueous solvent and an electrolyte salt dissolved in the nonaqueous solvent is preferably used as the nonaqueous electrolyte.
[0083] The non-aqueous solvent can be appropriately selected from known non-aqueous solvents. Examples of the non-aqueous solvent include carbonates, carboxylates, phosphates, sulfonates, ethers, amides, and nitriles. The non-aqueous solvent may be a compound in which some of the hydrogen atoms contained in these compounds are replaced with halogen. One or more non-aqueous solvents can be used.
[0084] The non-aqueous solvent preferably contains carbonate, and more preferably has carbonate as a main component. In the non-aqueous electrolyte storage element according to one embodiment of the present invention, when a non-aqueous solvent containing carbonate as a main component is applied, it is considered that a coating derived from carbonate is formed on the positive electrode surface. Then, it is considered that a charge / discharge reaction occurs in the positive electrode due to solid-phase diffusion through this coating. When the content of carbonate in the non-aqueous solvent is high, a good coating is sufficiently formed on the positive electrode surface, and it is considered that the above-mentioned effects related to the initial discharge capacity and the high-rate discharge performance after the charge / discharge cycle are further enhanced. The lower limit of the content of carbonate in the non-aqueous solvent is preferably 50% by volume, more preferably 70% by volume, even more preferably 90% by volume, and even more preferably 95% by volume. The upper limit of the content of carbonate in the non-aqueous solvent may be 100% by mass. The content of carbonate in the non-aqueous solvent can be a combination of any of the above-mentioned lower limits and the above-mentioned upper limit.
[0085] Examples of carbonates include cyclic carbonates and chain carbonates, and cyclic carbonates are preferred. The cyclic carbonate refers to a carbonate having a ring structure containing a carbonate group (-OC(=O)-O-). The lower limit of the content of the cyclic carbonate in the non-aqueous solvent is preferably 50% by volume, more preferably 70% by volume, even more preferably 90% by volume, and even more preferably 95% by volume. The upper limit of the content of the cyclic carbonate in the non-aqueous solvent may be 100% by mass. The content of the cyclic carbonate in the non-aqueous solvent can be a combination of any of the above lower limits and the above upper limit.
[0086] The cyclic carbonate preferably contains at least one selected from the group consisting of fluorinated cyclic carbonates and unsaturated cyclic carbonates, and more preferably contains both a fluorinated cyclic carbonate and an unsaturated cyclic carbonate.
[0087] The fluorinated cyclic carbonate refers to a compound in which some or all of the hydrogen atoms of a cyclic carbonate are replaced with fluorine atoms. The fluorinated cyclic carbonate is preferably a fluorinated saturated cyclic carbonate. The fluorinated saturated cyclic carbonate refers to a fluorinated cyclic carbonate that does not have a carbon-carbon double bond or a carbon-carbon triple bond in the molecule.
[0088] Examples of the fluorinated cyclic carbonate include fluorinated ethylene carbonates such as fluoroethylene carbonate (FEC) and difluoroethylene carbonate (DFEC), fluorinated propylene carbonate, fluorinated butylene carbonate, fluorinated vinylene carbonate, etc. Among these, fluorinated ethylene carbonate is preferred, and FEC is more preferred.
[0089] The content of the fluorinated cyclic carbonate in the non-aqueous solvent is preferably from 10 to 90% by volume, more preferably from 20 to 80% by volume, and even more preferably from 30 to 70% by volume.
[0090] The unsaturated cyclic carbonate refers to a cyclic carbonate having a carbon-carbon double bond or a carbon-carbon triple bond in the molecule. The unsaturated cyclic carbonate preferably has a carbon-carbon double bond in the molecule. The unsaturated cyclic carbonate may have a carbon-carbon double bond or a carbon-carbon triple bond in the ring structure or in a portion other than the ring structure, but preferably has the bond in the ring structure. The unsaturated cyclic carbonate may be fluorinated or may not be fluorinated, but preferably is not fluorinated.
[0091] Examples of the unsaturated cyclic carbonate include vinylene carbonate (VC), methyl vinylene carbonate, ethyl vinylene carbonate, propyl vinylene carbonate, butyl vinylene carbonate, dimethyl vinylene carbonate, diethyl vinylene carbonate, dipropyl vinylene carbonate, and vinyl ethylene carbonate, with VC being preferred.
[0092] The content of the unsaturated cyclic carbonate in the non-aqueous solvent is preferably from 10 to 90% by volume, more preferably from 20 to 80% by volume, and even more preferably from 30 to 70% by volume.
[0093] The lower limit of the total content of the fluorinated cyclic carbonate and the unsaturated cyclic carbonate in the non-aqueous solvent is preferably 50% by volume, more preferably 70% by volume, even more preferably 90% by volume, and even more preferably 95% by volume.The upper limit of the total content of the fluorinated cyclic carbonate and the unsaturated cyclic carbonate in the non-aqueous solvent may be 100% by mass.The total content of the fluorinated cyclic carbonate and the unsaturated cyclic carbonate in the non-aqueous solvent can be a combination of any of the lower limits and the upper limit described above.
[0094] As the cyclic carbonate, cyclic carbonates other than fluorinated cyclic carbonates and unsaturated cyclic carbonates, such as ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), and chloroethylene carbonate, can also be used.
[0095] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate, and bis(trifluoroethyl) carbonate.
[0096] The electrolyte salt can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, onium salts, etc. Among these, lithium salts are preferred.
[0097] The lithium salt is LiPF 6 , LiPO 2 F 2 , LiBF 4 , LiClO 4 , LiN(SO 2F) 2 inorganic lithium salts such as lithium oxalate (LiBOB), lithium difluorooxalate (LiFOB), lithium bis(oxalate) difluorophosphate (LiFOP), and other lithium oxalates; LiSO 3 CF 3 , LiN(SO 2 CF 3 ) 2 , LiN(SO 2 C 2 F 5 ) 2 , LiN(SO 2 CF 3 )(SO 2 C 4 F 9 ), LiC(SO 2 CF 3 ) 3 , LiC(SO 2 C 2 F 5 ) 3 Among these, inorganic lithium salts are preferred, and LiPF 6 and LiN(SO 2 F) 2 is more preferred, LiN(SO 2 F) 2 is more preferable. Also, LiN(SO 2 F) 2 , LiN(SO 2 CF 3 ) 2 , LiN(SO 2 C 2 F 5 ) 2 , LiN(SO 2 CF 3 )(SO 2 C 4 F 9 It is also preferred that the imide salt is an imide salt such as
[0098] The content of electrolyte salt in the non-aqueous electrolyte or non-aqueous electrolyte is 0.1 mol / dm 3 More than 2.5mol / dm 3 It is preferable that the value is 0.3 mol / dm or less.3 More than 2.0mol / dm 3 More preferably, it is 0.5 mol / dm or less. 3 More than 1.7mol / dm 3 More preferably, it is 0.7 mol / dm or less. 3 More than 1.5mol / dm 3 By setting the content of the electrolyte salt within the above range, the ionic conductivity of the nonaqueous electrolytic solution or the nonaqueous electrolyte can be increased.
[0099] The non-aqueous electrolyte may contain additives in addition to the non-aqueous solvent and the electrolyte salt. Examples of the additives include aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, and cyclohexanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, methyl methanesulfonate, and busulfan. Examples of the additives include sulfane, methyl toluenesulfonate, dimethyl sulfate, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridinium disulfide, 1,3-propene sultone, 1,3-propane sultone, 1,4-butane sultone, 1,4-butene sultone, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, lithium monofluorophosphate, lithium difluorophosphate, etc. These additives may be used alone or in combination of two or more.
[0100] The content of the additive contained in the non-aqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By setting the content of the additive within the above range, it is possible to improve the capacity retention performance or cycle performance after high-temperature storage, and to further improve safety.
[0101] The non-aqueous electrolyte may be a combination of a non-aqueous electrolyte solution and a solid electrolyte. The solid electrolyte may be selected from any material that has lithium ion conductivity and is solid at room temperature (for example, 15°C to 25°C). Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, halide solid electrolytes, and polymer solid electrolytes.
[0102] The shape of the nonaqueous electrolyte storage element of this embodiment is not particularly limited, and examples thereof include a cylindrical battery, a prismatic battery, a flat battery, a coin battery, and a button battery.
[0103] Fig. 1 shows a nonaqueous electrolyte storage element 1 as an example of a prismatic battery. The figure is a see-through view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a prismatic container 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51.
[0104] <Electricity storage device> The nonaqueous electrolyte storage element of the present embodiment can be mounted as an electricity storage unit (battery module) comprising a plurality of nonaqueous electrolyte storage elements assembled together in automobile power sources such as electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc., power sources for electronic devices such as personal computers and communication terminals, or power storage power sources, etc. In this case, the technology of the present invention may be applied to at least one of the nonaqueous electrolyte storage elements included in the electricity storage unit.
[0105] 2 shows an example of an electricity storage device 30 in which electricity storage units 20, each of which is an assembly of two or more electrically connected nonaqueous electrolyte electricity storage elements 1, are further assembled. The electricity storage device 30 may include a bus bar (not shown) that electrically connects two or more nonaqueous electrolyte electricity storage elements 1, a bus bar (not shown) that electrically connects two or more electricity storage units 20, and the like. The electricity storage unit 20 or the electricity storage device 30 may include a status monitoring device (not shown) that monitors the status of one or more nonaqueous electrolyte electricity storage elements.
[0106] <Method of Manufacturing Nonaqueous Electrolyte Storage Element> The method for producing the nonaqueous electrolyte storage element of the present embodiment can be appropriately selected from known methods, and includes, for example, preparing a positive electrode, preparing a negative electrode, preparing a separator, preparing a nonaqueous electrolyte, producing an electrode assembly using the positive electrode, the negative electrode, and the separator, and housing the electrode assembly and the nonaqueous electrolyte in a container.
[0107] The specific and preferred forms of the positive electrode to be prepared are the same as those of the positive electrode for a non-aqueous electrolyte storage element according to one embodiment of the present invention described above. Preparing the positive electrode may be manufacturing the positive electrode. The manufacturing of the positive electrode can be performed by the method described above.
[0108] The specific form and preferred form of the prepared negative electrode are the same as the specific form and preferred form of the negative electrode included in the nonaqueous electrolyte storage element according to one embodiment of the present invention described above. Preparing the negative electrode may be manufacturing the negative electrode. The negative electrode having metallic lithium can be manufactured by laminating a negative electrode active material layer containing metallic lithium directly or via an intermediate layer on a negative electrode substrate, and pressing or the like. The negative electrode active material layer containing metallic lithium may be a pure metallic lithium foil or a lithium alloy foil. The negative electrode can also be manufactured using a negative electrode mixture paste, as in the case of manufacturing the positive electrode.
[0109] The specific form and preferred form of the nonaqueous electrolyte to be prepared are the same as the specific form and preferred form of the nonaqueous electrolyte included in the nonaqueous electrolyte storage element according to one embodiment of the present invention described above. Preparing the nonaqueous electrolyte may be preparing the nonaqueous electrolyte. The preparation of the nonaqueous electrolyte can be performed, for example, by mixing an electrolyte salt and a nonaqueous solvent.
[0110] The electrode assembly can be produced by stacking or winding a positive electrode and a negative electrode with a separator interposed therebetween.
[0111] The method of housing the non-aqueous electrolyte in the container can be appropriately selected from known methods. For example, when a non-aqueous electrolyte solution is used as the non-aqueous electrolyte, the non-aqueous electrolyte solution may be injected through an injection port formed in the container, and then the injection port may be sealed.
[0112] The manufacturing method may include carrying out initial charging and discharging of an undischarged nonaqueous electrolyte storage element. In the case of a lithium-sulfur battery, for example, the initial charging and discharging is usually started with discharging. As described above, the first discharging is also called chemical conversion treatment. The number of charging and discharging in the initial charging and discharging is not particularly limited. For example, when a nonaqueous solvent containing carbonate is used, a good coating is formed on the surface of the positive electrode by reacting a part of the positive electrode with the nonaqueous electrolyte through the initial charging and discharging or chemical conversion treatment.
[0113] <Other embodiments> The positive electrode for a nonaqueous electrolyte storage element, the manufacturing method for a positive electrode for a nonaqueous electrolyte storage element, and the nonaqueous electrolyte storage element of the present invention are not limited to the above-mentioned embodiments, and various modifications may be made within the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.
[0114] In the above embodiment, the nonaqueous electrolyte storage element is used as a chargeable and dischargeable nonaqueous electrolyte secondary battery (e.g., a lithium-sulfur battery), but the type, shape, size, capacity, etc. of the nonaqueous electrolyte storage element are arbitrary. The present invention can also be applied to various secondary batteries, capacitors, etc.
[0115] In the above embodiment, the electrode assembly in which the positive electrode and the negative electrode are stacked with a separator interposed therebetween has been described, but the electrode assembly may not include a separator. For example, the positive electrode and the negative electrode may be in direct contact with each other in a state in which a non-conductive layer is formed on the active material layer of the positive electrode or the negative electrode. EXAMPLES
[0116] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0117] [Example 1] (Production of positive electrodes) A sulfur-based active material, sulfur elemental material and porous carbon, were mixed in a mass ratio of 70:30. This mixture was placed in a sealed electric furnace. After argon flow for 1 hour, the temperature was increased to 150°C at a rate of 5°C / min and held for 5 hours, and then allowed to cool to 80°C, the temperature at which sulfur elemental material solidifies. Thereafter, the temperature was increased again to 300°C at a rate of 5°C / min and held for 2 hours for heat treatment to produce a composite (sulfur-porous carbon composite: SPC). A positive electrode mixture paste was prepared using water as a dispersion medium, containing the composite obtained above, acetylene black and CNT as conductive agents, CMC as a dispersant, and a binder in a mass ratio of 93.0:1.5:0.2:0.3:5.0 as solid content. For the binder, a water-soluble binder, polyacrylic acid (PAA), and a water-dispersible rubber, styrene-butadiene rubber (SBR), were used in a mass ratio of 50:50. The prepared positive electrode mixture paste was applied to an aluminum positive electrode substrate (average thickness 15 μm) and dried. Note that the mass per unit area of the positive electrode active material layer after drying the dispersion medium was 15 mg / cm per side. 2The amount of the positive electrode mixture paste applied was adjusted so that the positive electrode active material layer was laminated on the positive electrode substrate.
[0118] (Preparation of the negative electrode) As the negative electrode, a pure metallic lithium foil (average thickness 600 μm) was prepared.
[0119] (Preparation of non-aqueous electrolyte) Fluoroethylene carbonate (FEC) as a fluorinated cyclic carbonate and vinylene carbonate (VC) as an unsaturated cyclic carbonate were mixed in a volume ratio of 50:50 in a nonaqueous solvent, and LiN(SO) was added as an electrolyte salt. 2 CF 3 ) 2 to 1.0 mol / dm 3 A non-aqueous electrolyte was prepared by adding the above-mentioned components in an amount of 0.1 to 100% by weight.
[0120] (Assembly of non-aqueous electrolyte storage element) The separator was prepared by laminating inorganic particle layers on both sides of a polyethylene microporous film. The positive electrode, negative electrode, separator and nonaqueous electrolyte were used to obtain a nonaqueous electrolyte storage element of Example 1.
[0121] [Examples 2 to 4, Comparative Example 1] Each of the nonaqueous electrolyte storage elements of Examples 2 to 4 and Comparative Example 1 was obtained in the same manner as in Example 1, except that the mass ratio of PAA and SBR used as the binder in the positive electrode active material layer was as shown in Table 1.
[0122] [Example 5] A nonaqueous electrolyte storage element of Example 5 was obtained in the same manner as in Example 2, except that the mass ratio of the composite, acetylene black, CNT, CMC and binder as solid contents in the positive electrode mixture paste was 92.0:1.5:0.2:0.3:6.0.
[0123] [evaluation] (Measurement of initial discharge capacity) For each of the obtained nonaqueous electrolyte storage elements of Examples 1 to 5 and Comparative Example 1, first, constant current discharge was performed at a discharge current of 0.1 C and a discharge cut-off voltage of 1.0 V as a chemical conversion treatment. Then, constant current / constant voltage charging was performed with a charging current of 0.1C and a charge cutoff voltage of 3.0V. The charge was terminated until the total charge time reached 30 hours. Next, constant current discharging was performed with a discharge current of 0.1C and a discharge cutoff voltage of 1.0V. A 10-minute pause was provided after discharge and charge. Discharging, charging, and pausing were all performed in a thermostatic chamber at 25°C. 1.0C was 1675mA / g in terms of current per mass of sulfur-based active material (sulfur alone). The quantity of electricity per mass of the sulfur-based active material (sulfur element) during the discharge after the above charging was determined as the initial discharge capacity (discharge capacity per mass of the sulfur-based active material). The results are shown in Tables 1 and 2. The results of Example 2 are shown in both Tables 1 and 2.
[0124] (Charge-discharge cycle test) For each of the nonaqueous electrolyte storage elements of Examples 1, 2, and 4 and Comparative Example 1 for which the above-mentioned "measurement of initial discharge capacity" was performed, a charge-discharge cycle test was carried out in the following manner. Constant current constant voltage charging was performed with a charging current of 0.1C and a charge cut-off voltage of 3.0V. The charge was terminated until the total charge time reached 15 hours. Next, constant current discharge was performed with a discharge current of 0.1C and a discharge cut-off voltage of 1.0V. A 10-minute pause was provided after discharge and charge. Discharge, charge and pause were performed in a thermostatic chamber at 25°C. 1.0C was defined as the current that could charge the initial discharge capacity per mass of the sulfur-based active material (sulfur alone) measured in the above "Measurement of initial discharge capacity" in 1 hour. The above charge and discharge were performed for 10 cycles. As the discharge capacity after the charge-discharge cycle, the discharge capacity at the 10th cycle per mass of the sulfur-based active material (sulfur alone) in the above-mentioned "charge-discharge cycle test" was determined. The results are shown in Table 1.
[0125] (High rate discharge test) For each of the nonaqueous electrolyte storage elements of Examples 1 to 4 for which the above-mentioned "measurement of initial discharge capacity" was performed, a high-rate discharge test was carried out in the following manner. First, constant-current constant-voltage charging was performed with a charging current of 0.1 C and a charge cut-off voltage of 3.0 V. The charge was terminated until the total charge time reached 15 hours. After that, constant-current discharging was performed with a discharging current of 0.1 C and a discharge cut-off voltage of 1.0 V. Next, constant-current constant-voltage charging was performed with a charging current of 0.1 C and a charge cut-off voltage of 3.0 V. The charge was terminated until the total charge time reached 15 hours. Thereafter, constant-current discharging was performed with a discharging current of 1.0 C and a discharge cut-off voltage of 1.0 V. A 10-minute pause was provided after discharge and charge. Discharge, charge, and pause were all performed in a thermostatic chamber at 25°C. 1.0C was defined as the current that could charge the initial discharge capacity per mass of the sulfur-based active material (sulfur alone) measured in the "Measurement of initial discharge capacity" above in one hour. The percentage of the discharge capacity at a discharge current of 1.0 C to the discharge capacity at a discharge current of 0.1 C in the "high rate discharge test" was calculated as the discharge capacity ratio (1.0 C / 0.1 C). The results are shown in Table 1. The higher the discharge capacity ratio, the better the high rate discharge performance.
[0126] [Table 1]
[0127] [Table 2]
[0128] As shown in Table 1, by setting the content of the water-soluble binder (PAA) to the binder to 50 mass% or more, the initial discharge capacity was 1,200 mAh / g or more, and the initial discharge capacity could be increased. In addition, the higher the content of the water-soluble binder to the binder, the higher the discharge capacity at the 10th cycle, the higher the discharge capacity after the charge / discharge cycle, and the higher the discharge capacity ratio, thereby improving the high-rate discharge performance. In addition, as shown in Table 2, the nonaqueous electrolyte storage element of Example 2, in which the content of the binder to the positive electrode active material layer is 5 mass%, had a larger discharge capacity than the nonaqueous electrolyte storage element of Example 5, in which the content of the binder to the positive electrode active material layer is 6 mass%. It was suggested that when the content of the binder to the positive electrode active material layer is 10 mass% or more, the initial discharge capacity of the nonaqueous electrolyte storage element does not become large. Furthermore, as shown in Table 1, the nonaqueous electrolyte storage elements of Examples 1 to 3, in which 50 mass % or more of the water-soluble binder (PAA) and the water-dispersible rubber (SBR) were used in combination as the binder, had a larger initial discharge capacity. [Industrial Applicability]
[0129] The present invention can be applied to nonaqueous electrolyte electricity storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles. [Explanation of symbols]
[0130] 1. Non-aqueous electrolyte storage element 2 Electrode body 3 containers 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device
Claims
1. A positive electrode active material layer including a sulfur-based active material and a binder is provided, The binder comprises a water-soluble binder, The content of the water-soluble binder relative to the binder is 50% by mass or more, A positive electrode for a nonaqueous electrolyte storage element, wherein the content of the binder relative to the positive electrode active material layer is 1% by mass or more and less than 10% by mass.
2. 2. The positive electrode for a non-aqueous electrolyte storage element according to claim 1, wherein the binder further comprises a water-dispersible rubber.
3. 3. The positive electrode for a nonaqueous electrolyte storage element according to claim 2, wherein a total content of said water-soluble binder and said water-dispersible rubber with respect to said binder is 90 mass % or more.
4. 3. The positive electrode for a non-aqueous electrolyte storage element according to claim 1, wherein the water-soluble binder is at least one selected from the group consisting of poly(meth)acrylic acid and salts thereof.
5. 4. The positive electrode for a non-aqueous electrolyte storage element according to claim 2, wherein the water-dispersible rubber is a diene rubber.
6. 3. The positive electrode for a non-aqueous electrolyte storage element according to claim 1, wherein the positive electrode active material layer further contains porous carbon forming a complex with the sulfur-based active material.
7. The method includes applying a positive electrode mixture paste containing a sulfur-based active material, a binder, and water; The binder comprises a water-soluble binder, The content of the water-soluble binder relative to the binder is 50% by mass or more, the content of the binder relative to the solid content in the positive electrode mixture paste is 1 mass % or more and less than 10 mass %.
8. A non-aqueous electrolyte storage element comprising the positive electrode for a non-aqueous electrolyte storage element according to claim 1 or 2.
9. The nonaqueous electrolyte storage element according to claim 8 , further comprising a negative electrode containing metallic lithium.
10. The nonaqueous electrolyte storage element according to claim 8 , further comprising a nonaqueous electrolyte containing a nonaqueous solvent mainly composed of carbonate.
Citation Information
Patent Citations
Positive electrode for lithium - sulfur battery
JP2003223897A